Influence of Infrastructure Development with its Sub-sectors on Economic Growth in Selected Asian Countries: An Empirical Analysis using DOLS and FMOLS Approaches - Batool, Komal; Akbar, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2023)
This paper exploits a dynamic ordinary least square (DOLS) and fully modified ordinary least square (FMOLS) panel data method to research the bond through infrastructure development and economic growth for four selected Asian countries viz., China, Pakistan, India and Bangladesh since 1990-2016. In this regard, the data is collected mainly from secondary resources including gross domestic product (GDP), domestic credit (DC), electric power consumption (EN), rail lines (RL), mobile subscriptions (M), health expenditures (HT), Education expenditures (ED). To attain the desired objectives, panel causality test is also used in the study to check the causal relationship among the variables. Results showed that all the variables have significant positive impact on economic growth except the variable domestic credit. Further, the findings showed that investment in all types of categories in public infrastructure have significant contribution in the development of the countries. The study concludes that an economy can robust its economic growth if regressive taxes are levied. Moreover, study recommends that the countries should have to focus on all the sectors but there is need to focus more on energy sector and telecommunication sector to accelerate economic growth.